Peran Pemerintah dalam Penanggulangan Perbaikan Gizi Berdasarkan Undang-Undang Republik Indonesia Nomor 36 Tahun 2009 tentang Kesehatan - Putra, Prima; Iriansyah, Iriansyah; Afrita, Indra (FORIKES, 2022)
Indonesia is a rich country but has health problems, one of which is unbalanced nutrition. The problems range from malnutrition to excess nutrition, even stunting cases are still high. The government has an important role to play in preventing this from getting worse. The role of the government as a facilitator, service implementer and regulator must be optimal to be accessible to the entire community. This study aims to analyze the role of the government in overcoming nutrition improvement based on the law through a literature study. This literature study uses three databases, namely PubMed, ScienceDirect and Google Scholar. The framework used in this literature review is PICOS (population, intervention, compare, outcome, study design) and exposure in the literature search using the PRISMA flow chart. The inclusion criteria for articles are full text in Indonesian or English and published in 2010-2020. This research is original research and examines government policies in health, especially the management of malnutrition. The author found eight articles that met the inclusion criteria. There are various types of government roles in overcoming nutrition improvement based on applicable laws and policies. Overall, from eight articles, it was found that the government's role is very important in overcoming nutrition improvement and there needs to be cross-departmental collaboration to be able to achieve the goal of optimal nutrition improvement.Keywords: The role of government; nutrition improvement; health policy ABSTRAK Indonesia merupakan negara yang kaya akan tetapi mempunyai masalah kesehatan salah satunya masalah gizi tidak seimbang. Permasalahannya mulai dari kurang gizi sampai dengan kelebihan gizi, bahkan kasus stunting juga masih tinggi. Pemerintah memiliki peranan penting dalam mencegah hal ini agar tidak semakin memburuk. Peran pemerintah sebagai fasilitator, pelaksana pelayanan dan regulator harus optimal untuk dapat diakses oleh seluruh masyarakat. Penelitian ini bertujuan untuk menganalisis peran pemerintah dalam penanggulangan perbaikan gizi berdasarkan undang-undang melalui studi literatur. Studi literatur ini menggunakan tiga database yaitu PubMed, ScienceDirect dan Google Scholar. Framework yang digunakan dalam literature review ini yaitu PICOS (population, intervension, compare, outcome, study design) dan pemaparan dalam pencarian literatur menggunakan diagram alir PRISMA. Kriteria inklusi artikel yaitu full text berbahasa Indonesia atau bahasa Inggris serta diterbitkan pada tahun 2010-2020. Penelitian merupakan original research dan menelaah kebijakan pemerintah dalam kesehatan terutama penanggulanagan gizi buruk. Penulis menemukan delapan artikel yang memenuhi kriteria inklusi. Terdapat berbagai jenis peran pemerintah dalam penanggulangan perbaikan gizi berdasarkan undang-undang dan kebijaknna yang berlaku. Secara keseluruhan dari delapan artikel didapatkan bahwa peran pemerintah sangat penting dalam penanggulangan perbaikan gizi dna perlu ada kerjasama lintas dinas untuk dapat mencapai tujuan perbaikan gizi yang optimal.Kata kunci: Peran pemerintah; perbaikan gizi; kebijakan kesehatan